2018
DOI: 10.1097/htr.0000000000000430
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Perceived Implementation Gaps for a Clinical Practice Guideline for the Rehabilitation of Adults With Moderate to Severe Traumatic Brain Injury

Abstract: Assessment of clinician perception provides a helpful perspective for implementation. Exploring perceived implementation gaps based on users' needs and expectation should be a part of an implementation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Journal of Head Trauma Rehabilitation/May-June 2021 not identified explicitly in the guidelines. 11,12 More importantly, the best PA approaches and exercise parameters to prescribe (eg, frequency, duration, intensity, intervention length, mode, timing to initiate, and progression of exercise) to facilitate recovery remain unclear. 2,6,13 For example, Howell et al 13 noted that important exercise dosage parameters were only reported in 5 of 11 studies comprising the review about PA interventions for individuals with mTBI.…”
mentioning
confidence: 99%
“…Journal of Head Trauma Rehabilitation/May-June 2021 not identified explicitly in the guidelines. 11,12 More importantly, the best PA approaches and exercise parameters to prescribe (eg, frequency, duration, intensity, intervention length, mode, timing to initiate, and progression of exercise) to facilitate recovery remain unclear. 2,6,13 For example, Howell et al 13 noted that important exercise dosage parameters were only reported in 5 of 11 studies comprising the review about PA interventions for individuals with mTBI.…”
mentioning
confidence: 99%
“…Adherence to the indicators was reported as percentages of facilities that reported the structure or process to be present. “Hard to meet” indicators were defined as those met by less than two-thirds of facilities [ 16 ]. Percentages of indicators met by each facility were also calculated to assess performance level.…”
Section: Methodsmentioning
confidence: 99%
“…15 Spinal Unit and Spinal Rehabilitation (SpiRe) Lab, IRCCS Fondazione S. Lucia, Rome, Italy. 16 University of Sydney, Sydney, NSW, Australia. 17 Division of Physical Medicine and Rehabilitation, Department of Medicine, University of British Columbia, Vancouver, BC, Canada.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…A number of guidelines have been published to promote best practices in care of persons with TBI, 32,33 but implementation is highly variable. 34 Sometimes erroneous services are applied because of lack of expertise and sometimes even those with expertise may apply improper or unnecessary services. Inaccurate diagnosis, inappropriate application of treatment at a particular stage of recovery, use of unproven or ineffective treatments, and application of effective treatment to those for whom it would not be of benefi t are examples.…”
Section: Realities Of the Marketplacementioning
confidence: 99%